2020
DOI: 10.1177/0253717620957524
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Telemedicine in Continuing Medical Education

Abstract: Continuing medical education (CME) is essential for medical practitioners to update their knowledge and skills periodically to provide clinical care in keeping with the evidence available. Traditional methods of CME such as workshops, conferences, and seminars are helpful to bridge the gaps in practice. With advancing technologies, online format is used to deliver CME with appropriate modifications. Although there are distinct advantages of online CME in regards to wider reach and flexibility, there are certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…As in other emergency situations, it is crucial to standardize the procedures, for example, having a checklist of indications for or contraindications to IVT and thrombectomy, or a checklist to remember each step of the digital procedure. The medical community needs Continuing Medical Education on such topics, which appear indeed very dynamic ( 22 ).…”
Section: Tactics For the Transitionmentioning
confidence: 99%
“…As in other emergency situations, it is crucial to standardize the procedures, for example, having a checklist of indications for or contraindications to IVT and thrombectomy, or a checklist to remember each step of the digital procedure. The medical community needs Continuing Medical Education on such topics, which appear indeed very dynamic ( 22 ).…”
Section: Tactics For the Transitionmentioning
confidence: 99%
“…Today, advances in technology open new prospects to create online programs to deliver CME with appropriate modifications [11]. e advent and rapid development of information and communication technologies (ICTs), especially the Internet and other related technologies, have created substantial changes in the global learning systems [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…e advent and rapid development of information and communication technologies (ICTs), especially the Internet and other related technologies, have created substantial changes in the global learning systems [2,12]. E-learning refers to the communication and learning activities through computers and networks or via electronic means [11]. e uses of e-learning in education systems have led to the creation of appropriate tools for the virtual CME [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…These web-based lectures are delivered and attended using computers and mobile devices, and at present several platforms are available to conduct these online sessions. These virtual activities offer the advantage of distance learning, cost-effectiveness, and flexibility with respect to time and place [ 8 ]. On the downside, information technology (IT) infrastructure and its related skills are required for conducting webinars.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that webinars solving daily clinical questions increase participants' uptake [ 12 ]. Other crucial elements to improve the learning experience are the pre-webinar orientation of the hosting platform and implementing clinical case discussions combined with informal quizzes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%